Antiemetic prophylaxis utilization in cancer patients in a hospital in Yogyakarta Special Region - Faridah, Imaniar Noor; Dyah Aryani Perwitasari; Siswandi; Lamhot B Simanjuntak; Suhendra, Gugun; Wulandari, Dewi; Dania, Haafizah; Rizky, Muhammad Arif; Islami, Safira Nur; Fatimah, Salma Auliya (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Chemotherapy is a type cancer treatment that uses anticancer drugs to inhibit cell division and kill cancer cells. Chemotherapy can cause side effect due to normal cells damages. The study aimed to investigate the use of antiemetic prophylaxis as premedication to prevent or reduce side effects on cancer patients undergoing chemotherapy. It was a observational study with retrospective design using medical records data of cancer patients who underwent chemotherapy in a hospital in Yogyakarta Special Region during May – September 2022. The results showed the cancer patients were dominated by women (85.71%) with ages 46-65 yr (63.27%) and stage III cancer (87.76%). There were 18 types of anticancer drugs and the most widely used drugs were doxorubicin 60 mg for the moderate emetogenic category and vinorelbine 37.5 mg for the low emetogenic category. The most widely used premedication regimen was a combination granisetron 3 mg, ondansetron 8 mg, and dexamethasone 10 mg regimen (72.45%). This combination was most often used for the cancer patients with the moderate emetogenic category (39 patients or 49.4%). However, not all the cancer patients undergoing chemotherapy with the low and moderate emetogenic anticancer drugs were administered the premedication. In conclusion, doxorubicin and vinorelbine are the most widely used for cancer patients undergoing chemotherapy in the hospital. In addition, a combination of granisetron, ondansetron, and dexamethasone is widely used as premedication.